Accelerating the update of a DL-based IDS for IoT using deep transfer learning - Idriss Idrissi; Mostafa Azizi; Omar Moussaoui (Institute of Advanced Engineering and Science, 2021)
Deep learning (DL) models are nowadays broadly applied and have shown outstanding performance in a variety of fields, including our focus topic of